Viola Xadrez: memórias, narrativas e prestígio - Fernandes, Michel Presley (2024)
Viola Xadrez, an artisanal factory founded half a century ago in the interior of São Paulo, and currently located in Catanduva/SP, urges us to reflecti about its trajectory. From its presence in specialized literature on peasant music, through sociology and anthropology studies on its construction techniques for stringed instruments, with an emphasis on peasant guitar, it demanded, however, a debate on its memories and historicity. In order to review the state of the art, this study promotes a dialogic construction between a Master's thesis on these techniques and transcriptions of extracts from three interviews; interviewees whose memories are linked to the history of Viola Xadrez from its beginnings to the present day. We seek to promote a hypothesis according to which the prestige that artisanal manufacturing pursues and also maintains among the consumer public has elements of explanation different to those achieved by the aforementioned anthropological studies. The dialogues between the sources serve as theoretical frameworks the notions of “liminality”, “memories” and “narratives”. The text ends with the search for the scientific construction of a “prestige concept”, likely to be applied to similar cases to Viola Xadrez.